PERAN AUDIT MANAJEMEN SUMBER DAYA MANUSIA TERHADAP KINERJA KARYAWAN INSTALASI RAWAT INAP DI RUMAH SAKIT (Studi Kasus pada Rumah Sakit Umum Daerah Dr. Soedirman Kebumen) - Susi Astuti (P4M STIE Putra Bangsa, 2018)
The development of hospital management, both from management and operational aspects is strongly influenced by various demands from the environment and technological progress, including the need for internal and external examination. Various problems arise along with hospital demands that must always improve its services, such as government regulations, financial management policies, the accuracy of information systems, the use of information technology, the adequacy of capital and Human Resources.The effectiveness and efficiency of health services such as care, treatment, examination, medical treatment, and other good diagnostics will affect patient satisfaction levels in the hospital. The management of the hospital is required to be able to plan, mobilize, organize, and coordinate the activities of professional and non-professional workers.The role of human resource functions towards the achievement of overall organizational goals will require an assessment and evaluation of the implementation of human resource programs developed in the function of each human resource. Assessment and evaluation conducted to find out all planned programs whether the implementation is maximal or not If indeed in practice has not been implemented with the maximum, it will look for solutions to overcome these problems. One way to assess this is to carry out management audits on human resource functions. Keywords: Management Audits, Human Resources, performance